Discovering the Model of Sufferings in Patients with Irritable Bowel Syndrome: A Qualitative Study - Khaki, Saeideh; Golparvar, Mohsen; Yousefi, Zahra (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study was conducted with the aim of discovering the model of sufferings in patients with IBS. Methods and Materials: The present research is qualitative in nature and was carried out using inductive thematic analysis. The research context and sample included interview transcripts from 18 patients with IBS who attended gastroenterology clinics in Isfahan. Semi-structured interviews and a thematic analysis results recording form were used to extract the sufferings of patients participating in the study. The interview texts were analyzed through the inductive thematic analysis method of Braun and Clarke (2019), alongside the calculation of the Content Validity Index (CVI) and the Content Validity Ratio (CVR). Findings: The findings indicated that the sufferings of patients with IBS encompass five final overarching themes: emotional and affective sufferings, sufferings related to reduced quality of life, existential and ontological sufferings, social sufferings, and cognitive and intellectual sufferings. Each of these five major themes also included a diverse range of sub-sufferings. Conclusion: Based on the findings of this study, the comprehensive model of sufferings in patients with IBS is suggested to be considered in future research as a foundation for psychometric studies (e.g., developing assessment tools to measure the intensity and extent of these sufferings) as well as in the implementation of comprehensive medical and psychological treatment interventions.